Social Embeddedness in Blangkon Business Development in Kampung Blangkon Protojayan Surakarta - Masayu, Florentina Galuh; Trinugraha, Yosafat Hermawan (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study aims to determine the embeddedness and social networks that develop in blangkon craftsmen in Kampung Blangkon Protojayan Surakarta and analyze the role of embeddedness and social networks in business development. This research uses a qualitative method with a case study approach. Embeddedness is divided into two, namely relational embeddedness and structural embeddedness. Relational embeddedness can be seen through relationships with family, consumers and neighbors of fellow blangkon craftsmen, through this relationship they can work together and maximize business capacity, while structural embeddedness can be seen through relationships with broader structures, namely the government and certain social institutions that provide a lot of assistance with tools and materials, training and market expansion. Social networks also develop and are related to embeddedness, craftsmen build their networks with various actors such as fellow craftsmen, raw material suppliers, government and certain social institutions. Embeddedness and maximally developed social networks play a major role in supporting the development of the blangkon business, through these two things, craftsmen obtain many positive benefits in the form of easy exchange of information as well as increasing business capacity through assistance with labor, capital, tools and materials, promotion and market expansion.